Adipsin Concentrations Are Associated with Back Pain Independently of Adiposity in Overweight or Obese Adults - Brady, Sharmayne R. E.; Mousa, Aya; Naderpoor, Negar; de Courten, Maximilian P. J.; Cicuttini, Flavia; de Courten, Barbora (Frontiers in Physiology, 2018)
Objective: To compare cardiometabolic risk factors including cytokine and adipokine concentrations between individuals with and without back pain. Methods: In 62 overweight/obese adults (BMI≥25kg/m2; 23F/39M), we collected data on: self-reported back pain; anthropometry (BMI, waist circumference, body composition [dual energy X-ray absorptiometry]); metabolic parameters (fasting glucose; insulin sensitivity [hyperinsulinaemic-euglycaemic clamps]); cardiovascular parameters (blood pressure, lipids); serum inflammation markers (high-sensitivity C-reactive protein [hsCRP; immunoturbidimetric-assay], tumour necrosis factor-alpha [TNF-α], interleukin (IL)-6, and IL-10 [multiplex-assay]); and adipokines (leptin, adipsin, resistin, and adiponectin [multiplex-assay]). Results: Participants who reported having back pain in the past month (n=24;39%) had higher BMI (mean±SD=33.8±6.3 vs. 30.2±4.1 kg/m2, p=0.008), fat-mass (39.9±12.3 vs. 33.9±9.8%, p=0.04) and waist circumference (109.6±16.8 vs. 101.0±9.3cm, p=0.01) compared to those without back pain (n=38;61%). No differences were observed in cardiometabolic parameters, inflammatory markers, or adiponectin or resistin concentrations. Those reporting back pain had higher adipsin concentrations compared to those without back pain (median [IQR]=744[472–2804] vs. 721[515–867] ng/ml, p=0.03), with a trend for higher leptin (5.5[1.5–24.3] vs. 2.3[1.5–6.7] ng/ml, p=0.05), both of which persisted after adjustment for age and sex. Adipsin remained associated with back pain independently of adiposity (BMI, waist, fat-mass, or total %body fat; all p≤0.03). Conclusions: Greater obesity, and higher adipsin and leptin concentrations were observed in those who reported back pain in the past month compared to those without back pain, and adipsin was associated with back pain independently of adiposity. Larger studies are needed to determine if adipsin could be a novel therapeutic target for prevention and/or treatment of back pain.